The association between incidence and mortality of brain cancer and human development index (HDI): an ecological study - Zaher Khazaei; Elham Goodarzi; Vahidreza Borhaninejad; Farhad Iranmanesh; Hosein Mirshekarpour; Batool Mirzaei; Hasan Naemi; Sayeed Maryam Bechashk; Isan Darvishi; Roghayeh Ershad Sarabi; Ahmad Naghibzadeh-Tahami (BMC, 2020)
Abstract Background Brain cancer is a rare and deadly malignancy with a low survival rate. The present study aims to evaluate the epidemiology of brain cancer and its relationship with the human development index (HDI) worldwide. Methods This is an ecological study. The data on cancer incidence and cancer mortality was extracted from the World Bank for Cancer in 2018 (GLOBOCAN 2018). The incidence, mortality rate, and brain cancer distribution maps were drawn for different countries. We used correlation and regression tests to examine the association of incidence and mortality rates of brain cancer with HDI. The statistical analysis was carried out by Stata-14 and a significance level of 0.05 was considered. Results According to the results of Global Cancer Registry in 2018, there were 18,078,957 registered cases of cancer in both sexes, of which 29,681 were related to brain cancer. The highest incidence (102,260 cases, 34.4%) and mortality (77,815 cases, 32.3%) belonged to very high HDI regions. Results showed that incidence (r = 0.690, P < 0.0001) and mortality rates (r = 0.629, P < 0.001) of brain cancer are significantly correlated with HDI. We also observed a positive correlation between brain cancer incidence and Gross National Income (GNI) (r = 0.346, P < 0.001), Mean Years of Schooling (MYS) (r = 0.64, P < 0.001), TABLE (LEB) (r = 0.66, P < 0.001) and Expected Years of Schooling (EYS) (r = 0.667, P < 0.001). Results also revealed that mortality rate was significantly correlated with GNI (r = 0.28, P < 0.01), MYS (r = 0.591, P < 0.01), LEB (r = 0.624, P < 0.01), and EYS (r = 0.605, P < 0.01). Conclusion The results of the study showed that the incidence and mortality of brain cancer in countries with higher HDI levels is higher than countries with lower HDI levels, so attention to risk factors and action to reduce it in countries with higher HDI levels in controlling this cancer in this Countries are effective.